Automatic diagnosis of premature ventricular contraction based on Lyapunov exponents and LVQ neural network. Issue 1 (October 2015) - Liu, Xiuling; Du, Haiman; Wang, Guanglei; Zhou, Suiping; Zhang, Hong
<x xml:space="preserve">Abstract</x> Highlights Based on the non-uniformity of RR interval, the premature beats can be diagnosed. The features with Lyapunov exponents of ECG beat are extracted. LVQ neural network is used to identify PVC beats.